2023
DOI: 10.1186/s43163-023-00430-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of COVID-19-associated mucormycosis patients and the clinical suspects: a descriptive audit

Abstract: Background India witnessed a massive surge of rhino orbital cerebral mucormycosis (ROCM) cases during the second wave of COVID-19, recording the highest number of cases in the world, indeed, an epidemic within the pandemic. Objectives To describe the clinical profile of patients with COVID-19-associated mucormycosis (CAM) and the clinical suspects for mucormycosis. Methods This single-center descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…This was similar to the finding of Singla et al, who reported an overall mortality rate of 33.9% [9]. Co-morbid conditions resulted in higher mortality, Amalanathan et al reported 49% mortality rates among patients with diabetes and mucormycosis [23]. Sahu et al also reported a mortality rate of 14% in patients presenting with diabetes or chronic kidney disease affected with mucormycosis [22].…”
Section: Discussionsupporting
confidence: 86%
“…This was similar to the finding of Singla et al, who reported an overall mortality rate of 33.9% [9]. Co-morbid conditions resulted in higher mortality, Amalanathan et al reported 49% mortality rates among patients with diabetes and mucormycosis [23]. Sahu et al also reported a mortality rate of 14% in patients presenting with diabetes or chronic kidney disease affected with mucormycosis [22].…”
Section: Discussionsupporting
confidence: 86%